BOMBAY DUCK FISHERY OF MAHARASHTRA WITH SPECIAL REFERENCE TO VBRSOVA - Bapat, S V; Alawani, S A (Indian Journal of Fisheries, 2011)
The Bombay duck fishery, confined mainly to Maharashtra and Gujarat, is supported by a single species, Harpodon nehereus. The annual landings averaged about 11,000 tonnes in early fifties, and rose to over 100,000 tonnes in late fifties but stabilised around 80,000 tonnes (forming about 10% of the annual marine fish catch of the country) from 1964 onwards. The Maharashtra catch stabilised around 30,000 tonnes in early sixties and the Gujarat catch around 50,000 tonnes in late sixties